Endoscopic Ultrasound-Guided Biliary Drainage Using Self-Expandable Metal Stent for Malignant Biliary Obstruction. (4th April 2017) - Lu, Lei; Tang, Xiaowei; Jin, Hangbin; Yang, Jianfeng; Zhang, Xiaofeng
Abstract : Purpose. Endoscopic ultrasound-guided biliary drainage (EUS-BD) has been increasingly reported worldwide. However, studies concerning EUS-BD from Mainland China are sporadic. This study aims to investigate the feasibility, efficacy, and safety of EUS-BD using SEMS in a single center from Mainland China. Methods. Between November 2011 and August 2015, 24 patients underwent EUS-BD using a standardized algorithm. Results. Three patients underwent rendezvous technique (RV), 4 underwent hepaticogastrostomy (HGS), and 17 underwent choledochoduodenostomy (CDS). The technical and clinical success rates were 95.8% (23/24) and 100% (23/23), respectively. Mean procedure time for the CDS group (35.9 ± 5.0 min) or HGS group (39.3 ± 5.0 min) was significantly shorter than that for the RV group (64.7 ± 9.1 min) (P < 0.05 ). Complications (13%) included (1) cholangitis and (2) postprocedure hemorrhage. During the follow-up periods (mean 6.4 months), 22 (91.7%) patients died of tumor progression with mean stent patency of 5.8 ± 2.2 months. Stent occlusion occurred in 2 (8.7%) patients. Conclusion. EUS-BD using SEMS is a feasible, effective, and safe alternative for biliary decompression after failed ERCP. EUS-RV may not be the first-line choice for EUS-BD in a medium volume center. Further evaluation and experience of this method are needed.